2020
DOI: 10.1002/smll.202006366
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine Triggered Surface and Lattice Regulation in Anatase TiO2−xFx Nanocrystals for Ultrafast Pseudocapacitive Sodium Storage

Abstract: Sodium‐ion batteries (SIBs) have been considered as one of the most promising secondary battery techniques for large‐scale energy storage applications. However, developing appropriate electrode materials that can satisfy the demands of long‐term cycling and high energy/power capabilities remains a challenge. Herein, a fluorine modulation strategy is reported that can trigger highly active exposed crystal facets in anatase TiO2−xFx, while simultaneously inducing improved electron transfer and Na+ diffusion via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The peak area of Zn 2p of the bleached state is far smaller than that of the coloration state, which confirms the (de-)insertion of Zn 2+ . Figure 3b shows that the Ti 2p 3/2 peak at the initial state can be divided into two peaks, corresponding to Ti 3+ 2p 3/2 and Ti 4+ 2p 3/2 , respectively, at 458.5 and 458.9 eV [8,46]. The calculated area ratio of Ti 3+ to Ti 4+ is 1/3, which is consistent with the fact that the TiO 2 matrix remains electrically neutral after Ti is replaced by high valence W. After being fully colored at 0 V, the peak of Ti 2p shifts to higher binding energy.…”
Section: Mechanism Analysis Of Zn 2+ -Based Electrochromic Of W-doped Tio 2 Ncsmentioning
confidence: 99%
“…The peak area of Zn 2p of the bleached state is far smaller than that of the coloration state, which confirms the (de-)insertion of Zn 2+ . Figure 3b shows that the Ti 2p 3/2 peak at the initial state can be divided into two peaks, corresponding to Ti 3+ 2p 3/2 and Ti 4+ 2p 3/2 , respectively, at 458.5 and 458.9 eV [8,46]. The calculated area ratio of Ti 3+ to Ti 4+ is 1/3, which is consistent with the fact that the TiO 2 matrix remains electrically neutral after Ti is replaced by high valence W. After being fully colored at 0 V, the peak of Ti 2p shifts to higher binding energy.…”
Section: Mechanism Analysis Of Zn 2+ -Based Electrochromic Of W-doped Tio 2 Ncsmentioning
confidence: 99%
“…In the equivalent circuit, R o is the ohmic resistance (total resistance of the electrolyte, separator, and electrical contacts), corresponding to the high-frequency intercept at Z' axis; R ct is the faradic charge-transfer resistance across the electrode/electrolyte interface, corresponding to the semicircle in the high-to-medium frequency region; Z W is the Warburg impedance related to ion diffusion in electrode, which is determined by the slope of the straight line at low-frequency region; and CPE is a constant phase element. [39,40] It is noted that the δ-MnO 2 /rGO electrode possesses much smaller R ct as compared to the δ-MnO 2 electrode, indicating a more efficient redox reaction in the 2D heterostructure. Moreover, the larger slope for the straight line of the δ-MnO 2 /rGO hybrid electrode suggests faster Zn 2+ ion diffusion in the hybrid electrode, agreeing well with the GITT results.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…Ni et al proposed a uorine modulation strategy to functionalize anatase TiO 2 nanocrystals. 113 It was found that the uorinated TiO 2 (TiO 2Àx F x ) nanocrystals exhibited a high ratio in the (001) facets, which are electrochemically reactive towards Na ions (Fig. 10d).…”
Section: Surface Functionalisationmentioning
confidence: 96%